Investigating the Links Between Body Composition and Female University Students’ Night Eating Habits and Sleep Quality - Rosli, Hanisah; Mat Ludin, Arimi Fitri; Lim, Amanda Priscilla; Vallavan, Vimalah; Sze Yuen, Lew; Yusop, Norizatul Hidayah; Razali, Nur Athirah; Amran, Amerull Daneal; Asmadi, Nurfarahin; Othman, Mohd Sham (UI Scholars Hub, 2022)
Background: Malaysia has the highest prevalence of obesity among Southeast Asian countries, and the current number is expected to increase further. In particular, the rate of obesity is reportedly increasing among females and young adults in Malaysia. Modern lifestyle habits, which include night eating and poor sleep quality, have been shown to increase the risk of obesity and high body fat. This study aims to determine the link between female university students’ body composition and their night eating habits and sleep quality. Methods: Body composition was measured using a Bioelectrical Impedance Analysis (BIA) analyzer. Night eating syndrome and sleeping pattern and quality were determined using the Night Eating Questionnaire (NEQ) and the Pittsburgh Sleep Quality Index (PSQI), respectively. Results: A total of 112 female students participated in this study, the majority (66.1%) of whom were categorized as having normal weight. Their body fat percentages (28.0 ± 6.1) were found to be lower than the standard value for Asian women. Most of the subjects were categorized as having normal night eating (93.8%) and poor sleep (76.8%) patterns. The correlation analysis results indicated significant relationships between sleep quality and night eating habit and body weight. Furthermore, analysis using binary logistic regression showed a protective relationship between muscle mass and sleeping habit. Conclusions: This study showed that the majority of the university students had poor sleep quality. This is an alarming finding. Therefore, further investigations on factors related to poor sleep quality among young adults are required.